Landslide Susceptibility Mapping Using a Fuzzy Approach. (2016) - Leonardi, Giovanni; Palamara, Rocco; Cirianni, Francis
Abstract: The present paper proposes a new methodology to characterize the landslide susceptibility of Reggio Calabria territory. The values obtained were classified into five categories and exported into GIS environment to produce a landslide susceptibility map. The principal objective of the proposed study is to identify the sections of the road network exposed to landslide hazards starting from the susceptibility map. To this aim, a fuzzy system was implemented for the assessment of the landslides susceptibility of the considered transport network.